An enhanced method for successful extraction of DNA from confiscated body fat of Himalayan black bear (Ursus thibetanus). (November 2021) - Yadav, Prabhaker; Gupta, Sandeep Kumar
Highlights: Recovery of prohibited animal fats was reported from north India. These were sent to us for the identification of species. Mitochondrial DNA cyt b and 16S rRNA gene-based molecular identification confirmed the Asiatic black bear species. We provided an enhanced protocol for the identification of species from the fat.